Stabilization of classic and quantum systems - Buts, V.A. (Вопросы атомной науки и техники, 2012)
It is shown that the mechanism of quantum whirligig can be successfully used for stabilization of classical systems. In particular, the conditions for stabilization of charged particles and radiation fluxes in plasma are found. Показано, что механизм квантовой юлы может быть эффективно использован для стабилизации классических систем. В частности, найдены условия стабилизации потоков заряженных частиц и потоков излучения в плазме. Доведено, що механізм квантової дзиґи може бути ефективно використовуватися для стабілізації класичних систем. Зокрема, знайдені умови стабілізації потоків заряджених часток та потоків випромінювання в плазмі.